The Two Faces of Nanomaterials Toxicity and Bioactivity - Han, Dong-Wook; Atabaev, Timur Sh (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Due to properties differing from those of larger materials, nanomaterials have been extensively used in different areas including nanomedicine, drug delivery, theragnosis, and bioimaging in recent years. Evaluating the toxicity profile (i.e., biocompatibility) of nanomaterials and their impact on health is essential to support the potential biomedical applications. This book deals with the two faces of nanomaterials, toxicity and bioactivity, hoping to aid with their development for clinical applications, reducing the possible risks associated with their use.